Vrednotenje organizacijskega modela meritev telesnih zmogljivosti SLOfit odrasli - Kramaršič, Jaka (Šport (Ljubljana), 2022)
Based on the abundant experience of systematic monitoring of physical fitness in childhood and adolescence, as well as domestic and foreign knowledge, we at the Faculty of Sports have designed the measurement battery SLOfit adults. The measurement, together with the support of the Moj SLOfit web application, allows the user to monitor physical fitness in adulthood. Important goals of establishing a test battery were the validity of measurement procedures and its feasibility in practice. Therefore, in May and June 2021, we conducted a pilot study to verify the planned organizational model of testing and execution of tests. The organizational model was evaluated using the feedback of the subjects (n = 324, 81% of all participants in the measurements), which was obtained by specially designed questionnaire with eight statements about the organisation of the measurements and with answers on a 7-point Likert scale (1 being the lowest mark). In addition, the organization of testing was qualitatively evaluated by observation. On average, the subjects rated the testing organization with 6.74 ± 0.31 points. Based on this mark, we conclude that the participants were very satisfied with the organization. However, the observation revealed some weaknesses in terms of safety of the participants and reliability of the tests; for that reason, we replaced the Sorenson test for torso strength partial curl-up, and the T-test for agility with figure-of-eight run test. The comparison with the organization using other test batteries showed significant advantages of SLOfit adult’s fitness test battery. Nevertheless, we will try to improve the organization and other parts of the system on the basis of newly gained experience in the future.
Keywords: antropometrija; gibalne sposobnosti; meritve; SLOfit; šport; telesne značilnosti